INCOME CONVERGENCE IN THE NEOCLASSICAL GROWTH MODEL: THE EXAMPLE OF THE WESTERN BALKAN STETES AND THE EUROPEAN UNION - Milutinović, Sonja (Poslovna ekonomija, 2023)
Income convergence represents catching up of countries with different development levels, i.e., faster income growth of the less developed countries then developed ones in a certain period of time. The income convergence hypothesis was first introduced by Robert Solow in his neoclassical growth model, based on the assumption of diminishing returns on capital. The subject of this paper is a theoretical presentation of income convergence in the neoclassical growth model, as well as an empirical analysis of the income convergence hypothesis. The paper will present absolute and relative income convergence through graphical and theoretical analysis. In addition, the paper will present previous research on income convergence, with empirical verification of the income convergence hypothesis on the example of the Western Balkan states and the European Union. The results of the regression analysis showed the existence of income convergence in the observed countries in the period 1995-2020.